2010
DOI: 10.1111/j.1369-7625.2010.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Health professionals, patients and chronic illness policy: a qualitative study

Abstract: Background and objective This study investigates health professionalsÕ reactions to patientsÕ perceptions of health issues -a littleresearched topic vital to the reform of the care of chronic illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 10 publications
2
50
0
Order By: Relevance
“…Another reasonable explanation for the high agreement was our homogenous sample of only hospital pharmacists working in Sydney West Area Health Service (SWAHS) but the data analysis of interviews conducted with other healthcare providers including doctors, nurses and allied health professionals in SWAHS and ACT revealed similar themes. That is, financial challenges, poor health literacy, seeking help inappropriately, and co-morbidities were linked with compliance; and a dysfunctional health care culture, inadequate access and lack of continuity were linked to fragmentation [13]. This suggest that the findings of this study are generalisable to other settings as well and that there is a need for joint interventions rather than specific interventions targeting pharmacists only.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Another reasonable explanation for the high agreement was our homogenous sample of only hospital pharmacists working in Sydney West Area Health Service (SWAHS) but the data analysis of interviews conducted with other healthcare providers including doctors, nurses and allied health professionals in SWAHS and ACT revealed similar themes. That is, financial challenges, poor health literacy, seeking help inappropriately, and co-morbidities were linked with compliance; and a dysfunctional health care culture, inadequate access and lack of continuity were linked to fragmentation [13]. This suggest that the findings of this study are generalisable to other settings as well and that there is a need for joint interventions rather than specific interventions targeting pharmacists only.…”
Section: Discussionmentioning
confidence: 50%
“…SCIPPS was designed to optimise chronic illness management in Australia through exploring the views of patients with chronic disease, their carers and healthcare providers, on incentives and barriers to optimal care. The results from interviews with patients and their carers have previously been reported [12], as have the views of healthcare providers on chronic illness management [13]. This article reports on the findings from group interviews and individual interviews with hospital pharmacists involved in the care of people with chronic illness.…”
Section: Introductionmentioning
confidence: 86%
“…Challenges with access to medical services are not unique to South Africa and reiterate the challenges that have been found elsewhere. A recent study in Australia echoes the high cost of medical services and emphasises that multi-provider care needs to be more accessible to individuals with chronic illnesses (Yen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent Australian study identified that consumers with chronic conditions experienced financial hardship and valued continuity of care [19], which was verified by health professionals in a follow-up study [20]. However, only consumers with specific conditions were included and the research was not specific to community pharmacy services [19].…”
Section: Introductionmentioning
confidence: 98%